The Plata Rock Avalanche: Deciphering the Occurrence of This Huge Collapse in a Glacial Valley of the Central Andes (33° S) - Moreiras, Stella M. (Frontiers in Earth Science, 2020)
This paper reviews the genesis of a chaotic deposit in the Blanco River basin (BRB) in the Argentine Andes that has been interpreted to be either of debris flow or glacial origin. A detailed sedimentological and geomorphic study of the deposit was undertaken to determine its origin. Glacial landforms in the source area of the deposit contrast markedly to those in neighboring valleys of the BRB. The lack of moraines and the presence only of rock glaciers in the headwaters of the Angostura Valley suggest that a glacier might have been destroyed by a rock avalanche in the Late Pleistocene. The deposit itself has the characteristics of rapid deposition by a huge (≤105 m3) rock avalanche sourced on the eastern slope of Mount Plata (5,956 m asl). The rock avalanche traveled a distance of 26.6 km and descended 4,700 m in altitude. The optically stimulated luminescence (OSL) ages on alluvial sediments associated with the landslide deposits suggest that the rock avalanche occurred ∼35–39 ka ago. The rock avalanche may have been triggered by an earthquake, given that the active Carrera fault system extends across the basin and there is a cluster of seven Late Pleistocene rock avalanches in the region.